ISOLATION AND CHARACTERIZATION OF INULINASE ENZYME-PRODUCING MICROBES FROM BANANA FRUIT (Musa paradisiaca) - Yusuf, Hadistiyani; Wijanarka, Wijanarka (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
Inulinase (EC 3.2.1.80) is an enzyme that can hydrolyze inulin into fructose or fructo-oligosaccharides. Using the inulinase enzyme as a catalyst in making inulinase-based fructose can obtain a fructose percentage of 90-95 percent. Inulin is a linear polysaccharide (ß-2,1-linked d-fructose residue terminated by a glucose residue) that accumulates as a storage carbohydrate in plants. One natural source that can produce inulin is bananas. Bananas are a source of inulin which contains around 0.58-1.09 percent. This research used three types of bananas, including Musa X paradisiaca, Musa paradisiaca formatypica, Musa paradisiaca var sapientum. Apart from that, you can also find out the characteristics of the microbes and enzyme activity produced from the three types of bananas. The results of this research show that the three isolated types of banana are capable of producing the inulin ase enzyme which is indicated by the growth of these microbes in ISM media. ISM media (Inulinase Selective Media) is an inulinase mixing media where only inulin-producing microbes can grow on the media. The microbes isolated from the three types of bananas that had the highest inulinase enzyme activity value were Raja Nangka bananas with an enzyme activity value of 0.405 IU/mL. Meanwhile, the lowest inulinase enzyme activity value was in Kepok bananas with an enzyme activity value of 0.088 IU/mL.